The Strange Demise of the Local in Local Government - Leach, Steve. author. aut Link
XIII, 129 p.
Keywords: This book challenges the notion that bigger local government is always better. Whilst the central government in Britain has often supported increases in local government size, the book argues that this has been detrimental, and has caused the erosion of distinctive community identities that were previously represented by local authorities empowered to make significant local choices about services and future strategy. Drawing from national and international evidence, it offers an alternative narrative about the size, role, function and purpose of local government to that currently dominating policy discussion. It aims to provide readers who oppose size increases in local government with the evidence and arguments to influence change in their areas. The book will appeal to policymakers working in central and local government, as well as academics interested in public policy, public administration and local government. Steve Leach is Emeritus Professor of Local Government at De Montfort University, England. Colin Copus is Emeritus Professor of Local Politics at De Montfort University, England and a Visiting Professor at the University of Ghent, Belgium.